2003
DOI: 10.2108/zsj.20.1231
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differentiation and Pubertal Development of Gonads in the Viviparous Mosquitofish, Gambusia affinis

Abstract: The ontogenetic development of gonads from embryo to adult was observed histologically in the viviparous teleost, Gambusia affinis. Primordial germ cells (PGCs) appeared in the subendodermal space of the embryo 14 days before birth, and then transferred to the dorsal mesentery to form paired genital ridges 12 days before birth. The PGCs proliferated in the genital ridge, forming gonadal primordia 10 days before birth. All gonadal primordia differentiated to the ovary containing oocytes 2 days before birth, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
3
25
0
6
Order By: Relevance
“…affinis remains one of the best candidates for biological control programs against mosquitoes [13,14]. This fish has been the subject of several studies including be- havioural ecology, histopathology, reproductive biology, endocrinology and toxicology [33][34][35]. The normal development of the ovaries has already been described [27,36] and the obtained data provide an experimental basis to study the activity of IGRs on females.…”
Section: Discussionmentioning
confidence: 99%
“…affinis remains one of the best candidates for biological control programs against mosquitoes [13,14]. This fish has been the subject of several studies including be- havioural ecology, histopathology, reproductive biology, endocrinology and toxicology [33][34][35]. The normal development of the ovaries has already been described [27,36] and the obtained data provide an experimental basis to study the activity of IGRs on females.…”
Section: Discussionmentioning
confidence: 99%
“…In other species, such as the perch (Lepori, 1980), the Atlantic halibut Hippogossus hippoglossus (Hendry et al, 2002), tilapia species Oreochromis (Nakamura and Takahashi, 1973;Nakamura et al, 1998), the common carp (Komen et al, 1992), and the goldfish, Carassius auratus (Nakamura, 1978) anatomical differentiation indicated by different types of ovarian cavity formation also precedes cytological differentiation of germ cells. However, in species such as the Japanese medaka (Satoh and Egami, 1972;Kanamori et al, 1985), the guppy, Poecilia reticulata (Miyamori, 1964), and the mosquitofish, Gambusia affinis (Koya et al, 2003) the opposite has been reported to occur. The process of primary oocyte growth (previtellogenesis) in the eelpout resembles that commonly described in teleost species (Bromage and Cumaranatunga, 1988;Tyler and Sumpter, 1996).…”
Section: Gonadal Sex Differentiationmentioning
confidence: 99%
“…No cyst of proliferating spermatogonia or spermatocytes indicating spermatogenesis was present. In other species, spermatogenesis begins later than in females, such as 40 -50 dph in Japanese medaka (Kanamori et al, 1985;Hamaguchi, 1992), e.g., 50 -70 dph in tilapia (Nakamura and Takahashi, 1973;Nakamura and Nagahama, 1989;Nakamura et al, 1998), 70 dph in mosquitofish (Koya et al, 2003), 90 -120 dph in fathead minnow (van Aerle et al, 2004), and 120 dph in common carp (Komen et al, 1992).…”
Section: Gonadal Sex Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambusia affinis (Koya et al 2003), Cichlasoma dimerus (Meijide et al 2005), zebrafish (von , Zoarces viviparus (Rasmussen et al 2006), rainbow trout (Vizziano et al 2007), the Adriatic sturgeon Acipenser naccarii (Grandi and Chicca 2008), and Gasterostus aculeatus (Lewis et al 2008).…”
Section: Gonadal Developmentmentioning
confidence: 99%